The Relationship Between Service Quality, Waiting Time, and Service Effectiveness on Patient Satisfaction - Lia Nur Amalina; Debora Natalia; Waynhena Sarawa Nesia (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Patient satisfaction and service quality are key indicators for assessing the performance of primary healthcare centers. Problems such as long waiting times, inconsistent service aspects, and varying service effectiveness can reduce patient satisfaction and affect service standard assessment. This study aimed to examine the relationships between service aspects, waiting time, and service effectiveness on patient satisfaction and service standard assessment. A quantitative approach with a cross-sectional design was used, involving 316 patients visiting the IMCI clinic, maternal and child health clinic, and general clinic in March 2025. Respondents were selected using proportional stratified quota sampling. Data were collected through a structured questionnaire and analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) in SmartPLS software, including both outer and inner model evaluations. The results showed significant positive relationships between service aspects, waiting time, and service effectiveness on patient satisfaction and service standard assessment. These findings provide a foundation for evidence-based quality improvement initiatives and can help identify priority areas for enhancing outpatient services.